Scientific and Pedagogical Significance of Information and Communication Technologies in the Process of Credit System in Education - Eshankulova Lola Sayfullayevna (International Journal on Integrated Education, 2022)
The process of development of higher education is closely connected with improving the quality of the process of training specialists, with dynamically developing research activities, the development of innovative education, with the social environment and economic needs of university research. Also, this process is aimed at improving the education system and information technology. In the conditions of the modern world, the primary task of the education system is the training of highly qualified specialists who meet all the requirements of modern reality. The article describes issues based on scientific and pedagogical significance of information and communication technologies in the process of credit system in education.